160 Ophthalmological involvement in m.3243A>G-related mitochondrial disease. Issue 9 (12th August 2022) - Devine, Helen; Ng, Yi; McFarland, Robert; Gorman, Grainne; Browning, Andrew
Abstract : Background: The m.3243A>G mtDNA is the most common pathogenic mtDNA variant and has a very varied clinical phenotype. Vision has a high metabolic demand and there are large numbers of mito- chondria in the retina, particularly in the photoreceptors and the retinal pigmented epithelial layer. Little is known about the heteroplasmic/phenotypic correlations of retinopathy in patients with m.3243A>G- related mitochondrial disease. Objective: The overall aim of the study was to explore retinal involvement in patients with m.3243A>G- related mitochondrial disease. Specifically, to describe the retinal and optic nerve changes and to determine whether the presence of maculopathy and/or optic nerve changes predict the development of CNS involvement in patients with the m.3243A>G mutation Methods: Patients with genetically confirmed m.3243A>G-related mitochondrial disease were identified from the UK Mitochondrial Disease Patient Cohort; a registry of patients under active follow up at one of the three UK Mitochondrial Centres (Newcastle, London and Oxford). Participants underwent detailed clinical and ophthalmological examination. Ophthalmological phenotype was correlated with a validated clinical rating scale score (NMDAS) and m.3243A>G heteroplasmy levels. Results: Retinal defects were common in m.3243A>G-related mitochondrial disease with subgroups of patients demonstrating maculopathy or optic nerve involvement. Conclusion: Characteristic retinal defects are common in m.3243A>G-related mitochondrial disease.